Inside the US Air Force - Boothroyd, Jennifer, 1972- (2018)
"They fly planes and help keep us safe, but how do they do it? Step behind the scenes to learn more about the US Air Force."--Provided by publisher.
What is the United States Air Force? -- Air Force training -- Air Force equipment -- The Air Force of the future -- Fighter pilot diagram -- United States Air Force history -- Glossary.
Includes bibliographical references and index.
Grades K-3.
Keywords: United States. -- Air Force -- Juvenile literature